Catalytic Enantioselective Intermolecular Benzylic C(sp3)−H Amination. (8th May 2019) - Nasrallah, Ali; Boquet, Vincent; Hecker, Alexandra; Retailleau, Pascal; Darses, Benjamin; Dauban, Philippe
Abstract: A practical general method for asymmetric intermolecular benzylic C(sp 3 )−H amination has been developed by combining the pentafluorobenzyl sulfamate PfbsNH2 with the chiral rhodium(II) catalyst Rh2 (S‐tfptad)4 . Various substrates can be used as limiting components and converted to benzylic amines with excellent yields and high levels of enantioselectivity. Additional key features for the reaction are the low catalyst loading and the ability to remove the Pfbs group under mild conditions to give NH‐free benzylic amines. Abstract : Benz an Benz : Ein Verfahren zur asymmetrischen intermolekularen benzylischen C(sp 3 )‐H‐Aminierung verwendet das Pentafluorbenzylsulfamat PfbsNH2 zusammen mit dem chiralen Rh(II)‐Katalysator Rh2 ( S ‐tfptad)4 . Vielfältige Substrate werden mit guten Ausbeuten und Enantioselektivitäten in benzylische Amine umgewandelt. Die Pfbs‐Gruppe kann unter milden Bedingungen entfernt werden, um die Amine mit freier NH‐Gruppe zu erhalten.